Membrane lipid composition defines membrane protein spectrum. Issue 4 (April 2023) - López-Lara, Isabel M.; Geiger, Otto
Abstract: In addition to glycerophospholipids, bacterial membranes often include amino acid-containing acyloxyacyl lipids. The functional implications of these aminolipids are largely unknown. However, a recent study by Stirrup et al . expands our understanding and shows that they are major determinants for membrane properties and the relative abundance of distinct membrane proteins in bacterial membranes.